The micro-politics of classroom talk: tracking students' shifting positions on race, place and privilege. Issue 3 (3rd July 2022) - Ferreira, Ana
ABSTRACT: For the socially conscious teacher working in diverse classrooms, conversation can surface and productively engage the politics of difference. Poststructuralist discourse analysis and/or positioning theory have provided insights into the students' subject positions and discourses in such conversations. However, studies are often limited by the use of brief extracts from lesson transcripts, making it difficult to detect how students are positioning one another and how subject positions shift over time. This article seeks to make a contribution by using extended extracts of moment-by-moment classroom talk to track the subject positions that students take up and map the discourses they draw on over time in an extended conversation. This qualitative case study examines classroom talk in a racially desegregated classroom in an elite school in South Africa. The issues that emerge provide insights into the ways in which students navigate discursive positions on race, place and privilege. Findings suggest that when the interactional order of the classroom is such that students' diverse knowledges and experiences are invited in, students collectively gain access to a multiplicity of discourses which can be used as resources to rethink their own subject positions and begin to imagine alternative positions from which to view their worlds.